Implementasi Rahmatan lil-alamin dalam Ekonomi Islam (Analisis Alokasi dan Distribusi Pendapatan Negara tentang Eksistensi (Brand Ekonomi Syariah dan Wakaf Tunai) di Indonesia) - Hisam Ahyani; Haris Maiza Putra; Dede Abdurohman; Naeli Mutmainah; Memet Slamet (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
The largest state income in Indonesia is tax. So it is necessary to study the allocation and distribution of these taxes from the perspective of Islamic economics, this is because Indonesia has the largest Muslim population in the world. Indonesian state income from an Islamic economic perspective is very important, this is because the Islamic economy in Indonesia currently has great opportunities in its development aspect. Especially at this time, it has been recorded in the history of the economy in Indonesia as evidence of the development of the Islamic economy in Indonesia, including the existence of the embodiment of the National Money Waqf Movement and the Islamic Economic Brand. The purpose of this study aims to reveal about: the allocation and distribution of state revenues from the perspective of Islamic Economics on Existence (Sharia Economic Brand and Cash Waqf); and its relevance in Indonesia in the current era (4.0). The method used in this research is library research whose sources are in the form of library data in the form of various books, journals, internet, and also other sources relevant to the theme of allocation and distribution of state income in Islam. The results show that the allocation and distribution of state revenues, when viewed from the perspective of Islamic Economics, has the concept of Rahmatan Lil 'Alamin, meaning equal distribution of ability or income for the community that can be applied in Indonesia, one of which is through the national movement of cash waqf and the Islamic economic brand.